HUBUNGAN POWER OTOT TUNGKAI DAN KECEPATAN REAKSI DENGAN TENDANGAN DEPAN PADA ATLET PUTRA PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE PEKANBARU - M. Irvan Ramadan; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations made by researchers of athletes who are Pencak Silat Persaudaraan Setia Hati Terate pekanbaru, there are still many players who fail at the kick. Failures that often occur when doing kicks such as: opponents easily bend off kicks, when kicks are often wrong and opponents often avoid, kicks often do not hit the opponent and slow to kick. This is supposed to be the cause of the physical condition of the athlete. The test in this study was to determine the relationship between leg muscle power and reaction speed with the forward kick on the athletes of the martial arts who are loyal to Terate pekanbaru. The population in this study were all athletes of the brotherhood of pencak silat persaudaraan setia hati terate pekanbaru with number 8. The sample in this study was 8 people who used the total sampling technique. The instruments in this study consist of a broad leap, a whole-body reaction, and a forward kick. The data obtained were analyzed using the correlation of the product moment. Based on the normality test, X1 produces data Lcount of 0.2558 and Ltable of 0.2850 and X2 produces Lcount of 0.1513 and Ltable of 0.2850. while the Y variable produces Lcount of 0.1689 and Ltable of 0.2850. And Y produces Lcount equal to 0.1423 and Ltable 0.2850 This means Lcount <LTable. The data is normally distributed based on statistical data analysis. Based on the requirement assessment described above, the hypothesis tests of variables X1 and X2 on variable Y data are 0.927 > 0.754 Rcount > Data table There is therefore a joint relationship between leg muscle strength and the speed of reaction to preliminary steps in the brotherhood of pencak silat. Persaudaraan Setia Hati Terate PekanbaruKey Words: Strength of leg muscles, speed of reaction, forward kick